Research on the Relationship between Characteristics of Video Bloggers and Consumers’ Purchase Intentions - Chong Zhang; Yueliang Liu; Ying Sun (Journal of Theoretical and Applied Electronic Commerce Research)
Video blogging channels for social media technology continue to innovate and evolve, and brands are beginning to rely on social media channels for product marketing. The factors influencing consumers’ purchase intention for products advertised by video bloggers are numerous and unclear. The main purpose of this study is to explore the mechanism by which the characteristics of video bloggers influence the formation of emotional cognition and then influences consumers’ purchase intention. Based on the SOR model, 518 questionnaires were administered to Chinese video blogging users. The AMOS 24.0 and SPSSAU 24.0 web tools were used to analyze the study data. Empirical results indicate that consumers’ perceived homogeneity, expertise, degree of emotional attachment to video bloggers, and perceived source confidence have a direct or indirect positive influence on purchase intentions. Evident advertising intention weakens the relationship between emotional attachment and purchase intention. This result is strategically important for a brand’s advertising efforts and market share and provides new research insights and frameworks for studying consumers’ advertised product purchase behaviors in the context of video blogging channels for social media.